Chronic inflammatory demyelinating polyneuropathy in a 13-year-old girl: A case report - Prajwol Pathak; Anil Pandey; Anu Gautam; Agrima Paudel; Muna Sharma; Sulav Neupane (Elsevier, 2024)
Introduction: Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) is a rare but treatable immune-mediated chronic disorder of the peripheral nervous system. We describe a pediatric female patient with CIDP who presented with progressive muscle weakness in both upper and lower limbs. Case presentation: A 13-year-old female, belonging to an indigenous group, presented with the complaint of difficulty in walking for 4 months. The weakness was bilaterally symmetrical involving distal muscles with no sensory loss. Cranial nerve examination showed bilateral sensory neural hearing loss. Electromyography and Nerve Conduction Test were both suggestive of neuropathy but ruled out myopathy. After the diagnosis of CIDP, IV Methylprednisolone, and Azathioprine was given, which improved her symptoms. Conclusions: A 13-year-old female was diagnosed with CIPD. With timely intervention, the CIDP in children has a better prognosis than in adults. CIDP should be suspected in cases of muscle weakness even in cases of pediatric female patients in order to avoid delayed diagnosis and treatment, which could affect the prognosis.